Synthesis and characterization of cyclophosphazene bearing chalcones derivatives - Nurzafira, Mahsir (Universiti Malaysia Sarawak, UNIMAS, 2008)
Chalcones is a type of compound which exists in plants, known to derive from flavonoids. With recent technology, there are many chalcones derivatives have been produced to improve its quality. Chalcones, yellow solid compounds was synthesized through aldol condensation by reacting acetophenone and alkylated 4-hydroxybenzaldehyde. Chalcones derivatives were then reacted with 1 mol cyclophosphazene, to produce mono-substituted and 6 mol of cyclophosphazene to give hexa-substituted phosphazene with chalcones derivatives. In spite of having various applications in pharmaceutical and medicine field, this compound is important in the technology of Liquid Crystal Displayed (LCDs) apparatus. This LCD quality can be improved by introducing cyclicphosphazene structure into its structure with the hope to give the flame retardant properties.